PERAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SMA - Umarih (MADINASIKA, 2021)
This research is motivated by the low performance of high school teachers, presumably due to the lack of proper supervision by the principal. The research aims to analyze and determine: a) The role of principal supervision in improving teacher performance; b). Benchmarks for determining the success of the supervisory role of the principal; c) Efforts by one school to improve the performance of high school teachers. The study used a qualitative approach with the main data collection tool using in-depth interviews with informants who were assigned a positive basis, the data obtained were analyzed through data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation techniques. The results showed: a) the principal has carried out his role and function as a supervisor based on the supervision program created with the supervisor; b) The benchmarks for the success of the principal's supervisory role are seen from the implementation of learning and the success of students in achieving learning goals. c) In improving teacher performance, the principal makes classroom observations, class administration checks, encourages teachers to be active in MGMP activities, and carries out clinical supervision. In conclusion, the role of principal supervision can improve teacher performance. High school.